2020
DOI: 10.1038/s41598-020-64888-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of Small Molecule MEIS Inhibitors that modulate HSC activity

Abstract: Meis1, which belongs to TALE-type class of homeobox gene family, appeared as one of the key regulators of hematopoietic stem cell (HSC) self-renewal and a potential therapeutical target. However, small molecule inhibitors of MEIS1 remained unknown. This led us to develop inhibitors of MEIS1 that could modulate HSC activity. To this end, we have established a library of relevant homeobox family inhibitors and developed a high-throughput in silico screening strategy against homeodomain of MEIS proteins using the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…It must be noticed that the use of the HXR9 in clinics has not been reported. Moreover, targeting the MEIS homeodomain by using small molecule derived from compound collections screenings seems effective 73 , but does not impair dimerization with PBX nor nuclear localization of MEIS.…”
Section: Suggestive Spatial Organizationmentioning
confidence: 99%
“…It must be noticed that the use of the HXR9 in clinics has not been reported. Moreover, targeting the MEIS homeodomain by using small molecule derived from compound collections screenings seems effective 73 , but does not impair dimerization with PBX nor nuclear localization of MEIS.…”
Section: Suggestive Spatial Organizationmentioning
confidence: 99%
“…These studies include the use of StemRegenin 1 (AhR antagonist), Garcinol (nonspeci c HAT inhibitor) and Nicotinamide (SIRT1 inhibitor) to reproduce human and mouse HSCs (Boitano et al, 2010;Peled et al, 2012;Singh et al, 2011). We have recently shown that the regulation of hematopoietic factors such as Meis1 and Hif-1a in HSCs and that these factors are needed for HSC quiescence (Kocabas et al, 2012)and targeting with MEIS inhibitors could allow ex vivo HSC expansion (Turan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…After 7 days of the treatment with the small molecules which are CHIR-99021, Pluripotin and DMSO as a control, lineage negative cells were labelled with Fc Blocker into 1X PBS then surface marker staining for APC-lineage cocktail, PE-C-kit, PE-Cy7-Sca-1 and FITC-CD34 (BD StemFlow Cat No 560492) according to the manufacturer's manual (Stemcell Technologies). The expressions of CD34 Sca-1 and c-Kit, surface markers in the labelled cells were analysed by ow cytometry (BD FACSARIA III) (Turan et al, 2020).…”
Section: Flow Cytometry Analysis Of Murine Hspcsmentioning
confidence: 99%
“…In a recent study, two small molecule MEIS1 inhibitors (MEISi-1 and MEISi-2) were identified using high-throughput in silico screening, and induced hematopoietic stem cell expansion ( 82 ).…”
Section: Meis1 Inhibitorsmentioning
confidence: 99%